Hypobetalipoproteinemia with accumulation of an apoprotein B-like protein in intestinal cells. Immunoenzymatic and biochemical characterization of seven cases of Anderson's disease. - Bouma, M E (1986)
We describe here seven cases (from five kindreds) of Anderson's disease, which is characterized by diarrhea, steatorrhea, hypobetalipoproteinemia with low levels of cholesterol, triglycerides, and phospholipids, and failure to secrete chylomicrons after a fat meal. Enterocytes isolated from intestinal biopsies of patients after overnight fast showed numerous fat droplets, a histological picture resembling that of abetalipoproteinemia. Immunoenzymatic staining of the enterocytes demonstrated large amounts of material that reacted with a polyclonal antiserum to apolipoprotein B. Further, the immunoreactive material was found to react with several different monoclonal antibodies capable of recognizing both the B100 and B48 forms of apoprotein B, but not with any of several monoclonal antibodies capable of recognizing only B100. This suggests that the material in the enterocytes is the B48 form of apoprotein B or a fragment thereof. Additional findings included decreased low density lipoprotein levels with an abnormal chemical composition, abnormal high density lipoprotein2 (HDL2) and HDL3 particle size distributions, and an abnormal HDL apoprotein composition. Increased amounts of proteins having electrophoretic mobilities similar to apo E and the E-AII complex were present. Finally, some cases exhibited additional protein components of apparent molecular weights between 17,000 and 28,000, which was similar to some cases of abetalipoproteinemia. These findings demonstrate that Anderson's disease is not due to the absence of synthesis of intestinal apo B and suggest that it is more complex than previously thought, affecting all the lipoprotein classes.